Stability of Money Demand Function in Nepal - Bhatta, Siddha Raj (Banking Journal, 2013)
<!--[if gte mso 9]> <![endif]--> This paper examines the long-run stability issue of money demand function in Nepal using the annual data set of 1975-2009 by using the recently developed ARDL modelling to cointegration popularized by Pesaran and Shin (1999). The bounds test shows that there exists the long-run cointegrating relationship among demand for real money balances, real GDP, and interest rate in case of both narrow and broad monetary aggregates. Further, the CUSUM and CUSUMSQ test reveal that both the long-run narrow and broad money demand functions are stable. The results show that demand for money balance in Nepal is a stable and predictable function of a few variables and the central bank can rely on the monetary aggregates as intermediate targets for achieving the broad economic objectives. DOI: http://dx.doi.org/10.3126/bj.v3i1.7508 Banking Journal Vol.3(2) 2013 pp.1-27 <!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} --> <!--[endif] -->